Development and validation of a new TRNSYS Type for thermosiphon flat-plate solar thermal collectors: energy and economic optimization for hot water production in different climates. (June 2019) - Kalogirou, S.A.; Agathokleous, R.; Barone, G.; Buonomano, A.; Forzano, C.; Palombo, A.
Abstract: This paper presents a new TRNSYS Type (called Type 99) which can be used for the energy assessment of thermosiphon Flat-Plate solar thermal Collectors (FPCs) for water heating. The accuracy of this new type is higher than the standard type (Type 45a) available in TRNSYS library, since the density and specific heat of water are estimated according to the operating fluid temperature. The results of a suitable experimental campaign are also presented for different commercial FPCs system layouts. The developed Type 99 is successfully validated, proven by the very good agreement achieved between the simulation and experimental results. By the new Type 99 a suitable Design of Experiment (DoE) analysis is carried out with the aim to assess the design and operating parameters mostly affecting the energy and economic performance of two types of FPCs. Specifically, collector pipe diameters, slope, storage tank volume, and thermal insulation thickness are investigated. The analysis is carried out for three case studies which refer to residential Domestic Hot Water (DHW) production applications and to three different European weather zones (Freiburg, Naples and Larnaca). For these case studies an optimization procedure is also carried out by varying the same design and operating parameters for two different objective functions: best energy behaviour [maximum Primary Energy Saving (PES)] and best economic performance [minimum Simple Pay Back (SPB)]. Interesting novel design criteria and encouraging economic results are obtained. Highlights: Development of a new TRNSYS Type for thermosiphon solar collectors. Experimental validation comparative analysis. Development of different case studies. Optimization procedure by Design of Experiment (DoE) analysis. Simple pay back assessment of different system configurations.